Genital Human Papillomavirus Infection in women from Florianópolis - Santa Catarina, Brazil - Fedrizzi, Edison Natal; Levi, José Eduardo (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Introduction: Human Papillomavirus (HPV) infection is the most common sexually transmitted infection in women. About 80% of sexually active women will have contact with this virus at some age in their lives. Most infections will be transient, but when the infection becomes persistent, associated with high oncogenic risk HPV, there may be progression to cancer, especially cervical cancer. The best way to prevent HPV infection is through the use of vaccines. Objective: To assess which are the most prevalent types of HPV in the city of Florianópolis, Brazil and if the majority of the diagnosed types are contained in the HPV vaccines currently available on the market and in the public health sector. Methods: More than 14,727 HPV tests were evaluated for the diagnosis of genital HPV infection in women from Florianópolis. The prevalence of infection was evaluated according to age of the women. HPV detection was performed using molecular biology tests, such as hybrid capture (for diagnosis of the HPV group, high or low oncogenic risk) and PCR (viral genotyping) techniques. Results: The diagnosis of HPV infection was made for women between one and 102 years of age. The highest positivity of the exams was observed in women aged 20–25 years (51% of the exams). The most prevalent age group was 31–35 years old (23.5%), and the lowest was for women aged 70 and above (0.6%). High oncogenic risk HPV was detected in 94.1% of positive samples and was the most frequent in all age groups. Mixed infection (high- and low-risk HPV) was more prevalent in the 66–70 age group (25.6%). The most frequent genotypes were non-16/18 high oncogenic risk HPV (77% of positive cases). HPV 16 was found in 17.1% of positive cases, and HPV 18 in 6.5%. Conclusion: The most prevalent types of HPV in Florianópolis in the last 6 years are non-16/18 high oncogenic risk HPV types, viral types not covered by the current HPV vaccine available in the public health sector in Brazil.